Manajemen Pembiayaan di Sekolah Menengah Pertama (SMP) Negeri 1 Lhokseumawe - Sari, Putri Novita (Medan Resource Center, 2024)
The purpose of financial management is to obtain and seek opportunities for funding sources for school activities, in order to use funds effectively and not violate the rules, and create transparent and accountable financial reports. The focus of this study is: 1). Planning, 2). Implementation, 3). Evaluation. This study uses a descriptive qualitative approach with a type of field research using data collection techniques: 1). Observation, 2). Interviews, 3). Documentation. The researcher obtained conclusions from this study, namely: 1). Financial Management Planning at SMP Negeri 1 Lhokseumawe was carried out with a general meeting attended by all principals, treasurers, and education personnel at the school to discuss future planning, then the principal or teacher held a member meeting again which was carried out as a follow-up to the general meeting held. Implementation schedule, time of implementation, place of implementation, and source of funds. 2). Implementation of Financial Management at SMP Negeri 1 Lhokseumawe according to information from the principal, there have never been any violations, so that everything can run smoothly according to the plan that has been made. In this case, the role of the coordinator of each standard is very important, because they are the ones who know best what each standard requires and what activities must be carried out to achieve the management of educational financing in schools. 3). Evaluation of Financing Management at SMP Negeri 1 Lhokseumawe ensures an effective and efficient way of working that leads the organization to the use of educational resources (human or labor, facilities and infrastructure, costs) efficiently and economically. It aims to find what is right and what is wrong, and to use the results of the evaluation to improve performance in the future.